Learning Methods And Strategies In Islamic Education - Abdul Aziz Romdhoni (Penerbit Hellow Pustaka, 2025)
Islamic education must view science and technology as the most important components of modern civilization, and studying them is an urgent necessity for the Islamic world if it does not want to be left behind. Furthermore, special attention should be paid to various modern sciences and techniques in the curriculum and various educational activities, but this must be in line with the spirit of Islam. The primary goal of Islamic education is to develop noble morals. Muslims, from the past to the present, have agreed that perfect moral education is the true goal of education. In teaching and learning activities, teachers require methods, and their use varies according to the desired objectives after the teaching process. A teacher will not be able to carry out their duties if they do not master any of the teaching methods formulated and proposed by psychologists and educational experts. Based on the above definition, the Islamic Religious Education (PAI) learning method can be defined as the method used by a religious teacher in the learning process to achieve goals in accordance with Islamic education.